Absence of detectable bovine leukemia virus miRNAs in human cancer small RNA-seq datasets - Jaworski, Juan Pablo (2026)
Bovine leukemia virus (BLV) encodes 10 mature microRNAs (miRNAs) that are highly expressed in infected cattle and have been implicated in oncogenic mechanisms. A potential association between BLV and human cancer remains controversial: while several reports have detected BLV proviral DNA in human breast tissue, high-throughput sequencing analyses have failed to identify BLV nucleic acids in human tumors. Here, we performed a high-sensitivity screen for BLV miRNAs across 335 publicly available human small RNA-seq data sets, including breast cancer (BCA), acute lymphoblastic leukemia, acute myeloid leukemia, chronic lymphocytic leukemia, and healthy controls, totaling approximately 1.98 billion trimmed reads. To validate our analytical workflow, six small RNA data sets from BLV-infected and uninfected cattle were processed in parallel. Across the human data sets, only 60 reads (0.000003%) aligned to BLV miRNA reference sequences, predominantly STAR strands or sequences containing mismatches—patterns consistent with background noise rather than biologically meaningful viral miRNAs. In contrast, BLV miRNAs were robustly detected across BLV-infected cattle samples, confirming pipeline sensitivity for canonical BLV miRNAs. These results demonstrate that BLV miRNAs are absent or below the operational detection threshold in human BCA and human leukemia miRNomes using standard small-RNA sequencing workflows and canonical reference sequences. IMPORTANCE